Proyecto de factibilidad para la implementación de una empresa de arreglo de prendas de vestir express para la ciudad de Loja - Córdova Pasaca, Liliana Maricela (2016)
This paper develops, interest and increased families to use the services of a settlement company clothing Express for the city of Loja, which aims to seek to meet the needs of families through the provision of settlement of their garments. To demonstrate the feasibility of the project different methods and techniques I was used to research permits, such as the Scientific Method, Inductive Method Deductive, Synthetic Analytical, statistical and techniques such as direct observation, information collection and survey; in order to carry out market research and to determine demand and supply. In the market study in the city of Loja, with a sample of 397 surveys to families of the city of Loja and 140 bidders engaged to provide services under clothing; Weighted surveys have been analyzed and have been inferred results then perform market analysis, determining potential demand for the first year is 40,140 families and Real Demand, 19,777 services Effective Demand is the determined services 835.38 arrangements. Unmet demand reflects the potential that exists in the city cited for this company, market with the following results: For the base year life of the project is unmet demand: 768,515 services. Within the technical study the installed capacity of the project will be 12,480 annual service, which for the first year 80% capacity so it is a new company and should consider introducing the service in the market is used is analyzed, so you obtain the capacity used to be for the first year of 9,984 services for the company to start its operation, then continues with the location of the company that is where the company and the operation of the plant will be located, then engineering is developed determining project process diagrams, characteristics of operation and management, technical requirements such as equipment, facilities, furniture and fixtures. Likewise an administrative study determined as a Limited Liability Company, and functional organizational structure to both legislative hierarchical levels, Executive, Consultant, Assistant Support, Operational and organizational charts and manuals functions performed; which they served as a pattern to implement a good organization, since it will have the following staff: Manager, a secretary, and 2 workers who will be part of the administrative staff and operational staff of the company. all costs that the project will be described in the financial study, ie investments in fixed assets $ 9.675,75; Deferred assets $ 2,152.50 and $ 3.860,51 in current assets, giving an investment of $ 15,688,76 and will be financed with contributions from partners 100% total investment. In the profit and loss in the first year a net profit of $ 5,048.62 will be obtained. In the breakeven sales of $ 37.329,16 originates with a capacity of 73, 46% in the first year of production. Within the financial evaluation presents the following results: according to Net Present Value of this project gives us a positive value of $ 12.314,50 indicating that having a positive NPV means that the value of the company will increase during stage of operation, the internal rate of return is 38,40%, and this satisfactory value for the project. Benefit Cost Ratio is $ 1.22 which means for every dollar invested project a gain of 0.22 cents will, the time required to recover the original investment will be 2 years, 8 months and 22 days for this project, the sensitivity coefficient is 0.99% which is within the limits of acceptance of the project, but supports an increase of 10,20% in costs and 8,40% in decreasing of the incomes.